Successful' development models in the MENA region - Imed Drine (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper provides a synthesis of the country cases in the Middle East and North Africa: Oman, Bahrain, Tunisia, and the United Arab Emirates. Although these countries differ in terms of resource endowments and economic evolution, they share common aspects of successful development. This chapter focuses on the developmental role played by good management of oil incomes, social cohesion, equitable distribution of oil resources, and political stability in Bahrain, Oman, and UAE, and human capital and trade openness in Tunisia. The chapter also discusses the major challenges faced by these countries, including particularly the need for political reforms, in order to achieve a higher and sustainable economic development. Finally, it draws some lessons for development.
Keywords: O11; E6; 330; MENA region; development policy; governance; Entwicklungspolitik; Governance-Ansatz; MENA-Staaten